Pregnancy in the rudimentary uterine horn - N. B. Kolesnikova; T. Yu. Marochko; A. S. Сhuikova; N. V. Artymuk (Фундаментальная и клиническая медицина)
Aim. To develop the methodology to assess the standards of physical development of children and adolescents.Materials and Methods. We have analyzed the available literature and our previous results to identify current problems in evaluating physical development of children with the focus on regional standards.Results. Current methodology in the field clearly needs standardization. We propose that “Standards of physical development of children and adolescents” software enables the objective evaluation of physical development in relation to children and adolescents and therefore can be suggested as a golden standard. Comparative analysis of the anthropometric data using this program and standard descriptive statistics (SPSS 21) showed the similarity of the results.Conclusions. Contemporary problems in the study of physical development of children and adolescents include the lack of standardized methods, standards, and official documents. We suggest our novel approach as a promising solution.